The effects of 9/11 on attitudes toward immigration and the moderating role of education - Simone Schüller (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The major event of the 9/11 terror attacks is likely to have induced an increase in anti-immigrant and anti-foreigner sentiments, not only among US residents but also beyond US borders. Using longitudinal data from the German Socio-Economic Panel and exploiting exogenous variation in interview timing throughout 2001, I find that the terror attacks in the US caused an immediate shift of around 40 percent of one within standard deviation to more negative attitudes toward immigration and resulted in a considerable decrease in concerns over xenophobic hostility among the German population. Furthermore, in exploiting within-individual variation this quasi-experiment provides evidence on the role of education inmoderating the negative terrorism shock.
Keywords: F22; I21; J61; 330; immigration; attitudes; education; September 11; terrorism